Analysis of Civic Knowledge Achievement through HOTS-Based Questions in Pancasila and Civic Education at the Elementary School Level - Puger Tegar Akbar Wibowo; Anita Trisiana; Sarafuddin (Madako Elementary School, 2026)
The limited ability of students to process civic knowledge at the HOTS analysis level, reflected in low performance in solving high-level reasoning problems, is the main focus of this study. This condition is closely related to Pancasila and Civic Education learning practices that are still dominated by LOTS-oriented questions, thus not optimally fostering students’ critical and reflective thinking skills. This study aims to analyze the achievement of civic knowledge through HOTS questions among fifth-grade students at SD Negeri Mojosongo 5 Surakarta using a qualitative case study approach. The clustering results show a distribution of 91.67% in the high category, 75% in the medium category, and 41.67% in the low category, indicating disparities in higher-order thinking skills. Research instruments included HOTS-based tests covering analysis, evaluation, and creation indicators, interview guidelines, and observation sheets, all validated by experts with a coefficient of ≥0.80. The findings reveal that high-category students demonstrate conceptual and argumentative elaboration, while low-category students remain at the level of factual understanding. Influencing factors include reading literacy, frequency of HOTS practice, and teachers’ pedagogical strategies, implying the need for systematic reorientation of HOTS-based  Pancasila and Civic Education learning.